If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4n+9=3n+5
We move all terms to the left:
4n+9-(3n+5)=0
We get rid of parentheses
4n-3n-5+9=0
We add all the numbers together, and all the variables
n+4=0
We move all terms containing n to the left, all other terms to the right
n=-4
| 3.5+1.2+x=8 | | 8p+64=4p-6 | | w/6+2.1=-17.1 | | p-10=35-2p | | 5(2x+1)=14x-(2x-1) | | -4w+10=-2w | | 75n=5 | | (10.5+m)/11.57=2.748 | | 10-6w=3-6w | | d-3=0.33 | | 2x−5x=21 | | 17x+6=4(4x+3) | | -9r+10=-7r-10 | | b-11=-19 | | x+5+1=15 | | 4(2x+7)=7x+9+x | | 7(z+2)=7+7z+6-2 | | -6x-3=2-1(5x+6) | | 10u=10u+10 | | 5x+7=−6x+73 | | 2(-18r-2)-11=-15 | | 5x+7=−6x+73. | | 4x/7-0.6=3.6/ | | 2/5y+y=30 | | 10x-7=-5x+38 | | 7m=8m-9 | | -3n=-7-3n | | 8+3x=3x-5 | | 2x+5=2(2+x) | | 2x=2(-8+3x) | | 3(x-1)=2x-7-3 | | (8x+-14)+(4x+1)=59 |